Analysis Difficulty Student in Read Understanding in Grade 3 Elementary School - Dearny Saragih, Regina Patricia (Journal of Social Science and Education Research, 2024)
This research uses Qualitative research through a case study approach. The purpose of the research is to find out students' difficulties in reading comprehension, the factors that hinder it, as well as overcoming students' difficulties and efforts to overcome them. The results showed that: 1. Students' difficulties in reading comprehension are lack of recognition of letters, difficulty distinguishing letters that are similar in shape, still spelling letters and sentences, reading speed is still intermittent, easy forgetting the words they have read, errors in pronunciation of words and omission of letters, still have to be guided, always tracing each line of reading with their fingers/writing tools, takes quite a long time when reading spelling; 2. Factors that hinder come from internal factors including lack of motivation and interest in reading and external factors including the environment where they live, family, and school; 3. Efforts to overcome them are by providing tutoring outside of class hours, teachers use special methods such as multisensory methods and varied learning media, parents must pay more attention and accompany their children when studying at home, establish a good working relationship between teachers and parents, and students must be more active in practicing learning to read comprehension. Based on the results of the study, it can be concluded that there are 2 students who have difficulty reading comprehension in class 3 of Tapos 4 State Elementary School, Depok City, even semester of the 2023/2024 academic year.